STUDI KOMPARATIF MANAJEMEN STRATEGIK SEKOLAH PENYELENGGARA PENDIDIKAN INKLUSIF - Adella Veranti; Rambat Nur Sasongko; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The purpose of this study to compare in general about the strategic management capabilities inclusive school education providers Public Elementary School 3 and Islamic Elementary School Al Aufa of Bengkulu city. The study method was comparative with qualitative descriptive approach. The technique of collecting data used interviews, observation and documentation. The results showed that the environmental analysis is concluded through a SWOT analysis. Strategy formulation has not considered internal and external environment and the needs of children with special needs that is an inclusive school. Implementation of the strategy is to do the elaboration of strategies have been formulated in the form of learning activities. The evaluation was done when the supervision of the teacher education inclusion classes. To Islamic Elementary School Al Aufa, Principal to plan follow-up activities for children with special needs. While in Public Elementary School 3 Principal only make any repair records.